Hydroformylation of 1-hexene using Rh/TPPTS complex exchanged on anion exchange resin: kinetic studies - Diwakar, Makarand M.; Deshpande, R. M.; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2005)
The exchange of the Rh/Triphenylphosphine trisulfonate sodium [TPPTS] complex on to an anion exchange resin results in a stable heterogenized catalyst for the hydroformylation of alkenes. The kinetics of hydroformylation of 1-hexene using Rh/TPPTS complex exchanged on anion exchange resin to Amberlite IRA-93 has been investigated for the first time. The rate of the reaction was found to be dependent on the partial pressure of hydrogen and 1-hexene concentrations with a first order. A maximum in the rate with increasing partial pressure of carbon monoxide was observed. A rate model has been proposed which predicts the observed rate data within reasonable error. The activation energy was found to be 84.37 kJ/mol. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: heterogenized catalyst; Hydroformylation; ion-exchange resin; kinetics; Rhodium

Hydroformylation of olefins using dispersed molecular catalysts on solid supports - Pagar, N. S.; Deshpande, R. M.; Chaudhari, Raghunath V. (Catalysis Letters, 2006)
A new method for heterogenization of metal complex catalysts by precipitation of its water-soluble analogue as a Gr.2 metals (Ca, Sr or Ba) salt on porous supports has been proposed. This technique yields a highly dispersed catalyst having a significantly higher activity (TOF) for hydroformylation of olefins compared to other known heterogenized catalysts. The catalyst can be recycled with ease.
Keywords: carbon support; Heterogenization; Hydroformylation; Olefins; Rhodium

Kinetics of hydroformylation of 1-octene in ionic liquid-organic biphasic media using rhodium sulfoxantphos catalyst - Deshpande, R. M.; Kelkar, Ashutosh A.; Sharma, A.; Julcour-Lebigue, C.; Delmas, Henri (Chemical Engineering Science, 2011)
Biphasic hydroformylation of 1-octene was performed using rhodium sulfoxantphos catalyst dissolved in [BuPy][BF(4)] ionic liquid. Preliminary experiments proved this system to retain the catalytic complex within the ionic liquid phase and to maintain a high selectivity towards the linear aldehyde (n:iso ratio of 30) over several cycles. Process parameter investigation showed a first order dependence of the initial rate with respect to the catalyst and 1-octene concentrations, but a more complex behavior with respect to hydrogen (fractional order) and carbon monoxide partial pressures (inhibition at high pressures). Different mathematical models were selected based on the trends observed and evaluated for data fitting. Also, rate models were derived from a proposed mechanism, using Christiansen matrix approach. To calculate concentrations of substrates in the catalytic phase as required by this kinetic modeling, solubility measurements were preformed for the gases (pressure drop technique), as well as for 1-octene and n-nonanal (thermogravimetry analysis). (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biphasic catalysis; Butylpyridinium tetrafluoroborate; kinetics; Parameter identification; Reaction engineering; solubility

Kinetics of hydrogenation of lauric acid in a batch slurry reactor using Ru-Sn/TiO2 catalyst - Shinde, S. B.; Deshpande, R. M. (Asian Journal of Chemistry, 2012)
Ru-Sn catalyst was prepared in-house by impregnation method. This catalyst was found to be stable for four recycles. The rate of hydrogenation of lauric acid (LAC) using Ru-Sn/TiO2 catalyst was found to be linearly dependent on catalyst loading, lauric acid concentration old hydrogen partial pressure. The rate data obtained from kinetic study were fitted to simple rate equation based on Langmuir-Hinshelwood (L-H) type model. Based on kinetic data the hydrogenation of lauric acid over Ru-Sn/TiO2 catalyst is proposed to occur by I dual site mechanism the activation energy for hydrogenation of lauric acid to lauryl alcohol (LAOH) using Rii-Sn/TiO2 catalyst was found to be 77.2 kJ/mol.
Keywords: Hydrogenation; kinetics; Langmuir-Hinshelwood model; Ru-Sn/TiO2 catalyst

Cinnamic acid derivatives via heck reaction in an aqueous-biphasic catalytic system with easy catalyst-product separation - Jagtap, Sangeeta Vijay; Deshpande, R. M. (Asian Journal of Chemistry, 2013)
A true biphasic [aqueous-organic] system for the coupling of water soluble sodium acrylate with different aryl halides for the synthesis of cinnamic acid derivatives has been developed, employing palladium catalysts that is soluble in organic phase. Amongst them, palladacycle was found to be stable in presence of water and could be recycled for four times with no loss in the activity. Such a system facilitates easy recycle of catalyst and also the removal of the salts from the catalyst phase, ensuring high activity with respect to cumulative turn over number (TON) and turn over frequency (TOF). The reaction was facilitated by organic as well as inorganic bases. The efficiency of the catalyst, role of organic/inorganic bases on the activity is reported.
Keywords: Biphasic catalysis; Heck reaction; Palladacycle; Separation

Insight into PdCl2(bipy) complex as an efficient catalyst for heck reaction and kinetic investigations in homogeneous medium - Jagtap, Sangeeta Vijay; Deshpande, R. M. (Kinetics and Catalysis, 2013)
PdCl2(bipy) complex (bipy = 2,2'-bipyrydine) efficiently catalyzes the vinylation of aryl halides. The activity of this catalyst for the Heck reactionwas demonstrated for a variety of aryl halides and olefins in the presence of different organic and inorganic bases. The catalyst is stable under the reaction conditions and no degradation was observed. The kinetics of the Heck coupling of styrene with iodobenzene using the PdCl2(bipy) complex with potassium acetate as a base was studied over a temperature range of 393-413 K in 2-nitro-2-methyl-1-propanol medium. An empirical rate model has been proposed to fit the observed data and is found to be in good agreement with experimental results. The activation energy of the reactionwas found to be 98.70 kJ/mol.

Highly efficient rhodium-phosphite catalyzed hydroformylation of camphene and other terpenes - Pagar, N. S.; Deshpande, R. M. (Asian Journal of Chemistry, 2019)